Perbedaan Kemampuan Empati Mahasiswa Keperawatan di Program Studi Ilmu Keperawatan Fakultas Kedokteran UGM - Anisa Hidayah; Martina Sinta Kristanti; Mariyono Sedyowinarso (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: Nurses are supposed to be able to show empathy to patients. Empathy is capability to feel the emotion, thought, and condition of the patient without involving self emotion. Capability of showing empathy in nurses is builtsince the period of education. Every stage in nursing education at nursing study program has different learning activities and load of materials. The difference may be affected by capability of showing empathy in students. The objective of this study is to identify difference in empathy capability of nursing students of Faculty of Medicine UGMMethod: This was a quantitative study with cross sectional design. Samples were taken through purposive proportional sampling involving 88 nursing students at Faculty of Medicine Universitas Gadjah Mada undergoing academic education (batch 2009 to 2012) and clinical education (batch 2007 and 2008). Empathy capability was assessed using Jefferson Scale of Physician Empathy – Nursing Student Version R (JSPE-R).Results: Average score of empathy capability was 113.26 with standard deviation 10.45. There was difference in empathy capability of students of batch 2007 to 2012 (p=0.014). Average score of empathy capability of the students decreased along with the duration of education. There was no difference in empathy capability based on gender (p=0.516), age (p=0.668), ethnic group (p=0.167), and stage of education (p=0.541). There was difference in score of standing in the patient shoes between academic and clinical students (p=0.022).Conclusion: There is difference in empathy capability in nursing students from different batch at Faculty of Medicine UGM.